Dehydration of young athletes: diagnostic methods, correction of blood rheology, water-electrolyte and acid-base balance using an isotonic specialized drink based on apian and herbal components - V. S. Kim; G. A. Prosekin; Yu. N. Fedosov; E. V. Lomazova; S. A. Parastaev (Sports medicine: research and practice, 2020)
Objective. To evaluate the hydration in young athletes after a 1-month intake of a specialized isotonic drink for children based on apian and herbal components F25 IsoDrink Light (IsoDrink-L).Materials and methods. From 76 young athletes under 18 years old, of which 70 from the Ugra boarding school of the Olympic reserve of Khanty-Mansiysk (ice hockey, swimming, skiing, biathlon) and 6 highly qualified swimmers from the St. Petersburg Swimming Center Petersburg, the main group included 42 athletes with a monthly course of IsoDrink-L. The control group included 34 people who used college rehydration methods (water and regularly purchased isotonic “X”). Hydration was studied using an impedance assessment of body composition, including the calculation of the total amount of fluid (TAF), as well as intracellular and extracellular fluid (Intracell. fluid and Extracell. fluid), the Extracell. fluid/TAF ratio and a survey of participants about the method of rehydration (water or isotonic). The biochemical composition of blood, specific gravity and color of morning urine before and after a monthly course of isotonics were also evaluated.Results. Bioimpedance measurement of the amount and ratio of body water in combination with an assessment of hematocrit, sodium, potassium, urea and lactate in the blood, as well as the specific gravity and color of morning urine made it possible to detect dehydration in all athletes before taking isotonic. The picture of dehydration in the form of cellular hyperhydration, extracellular hypohydration, hyponatremia, hypovolemia, blood “thickening and acidification” was detailed. A monthly course of isotonic demonstrated its efficiency, dehydration in athletes was eliminated. In the control group, no positive dynamics were noted, which raised the question of the inefficiency of the isotonic “X” and the harmfulness of water, which in 95 % of cases was used as a means of rehydration. The high efficiency of IsoDrink-L and the bioimpedance method was confirmed by the inverse correlation of ...